IMPACT OF ACADEMIC MOBILITY: THE LESSONS LEARNT - Oksana Zabolotna (Pavlo Tychyna Uman State Pedagogical University, 2017)
The results of the survey conducted among EMINENCE Project graduates (2012-2016) in the framework of Erasmus Mundus Programme had been revealed. The aim of the survey was to examine the project's results in the context of the following key positions: a post-project transition to training/work; practical orientation; quality of a training; quality of a research; the role of a university; competence; partnership and exchange of experience.